2008
DOI: 10.1186/1472-6890-8-6
|View full text |Cite
|
Sign up to set email alerts
|

Tiling array-CGH for the assessment of genomic similarities among synchronous unilateral and bilateral invasive breast cancer tumor pairs

Abstract: Background: Today, no objective criteria exist to differentiate between individual primary tumors and intra-or intermammary dissemination respectively, in patients diagnosed with two or more synchronous breast cancers. To elucidate whether these tumors most likely arise through clonal expansion, or whether they represent individual primary tumors is of tumor biological interest and may have clinical implications. In this respect, high resolution genomic profiling may provide a more reliable approach than conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…On the other hand, Teixera et al [21,22], using cytogenetic analysis, concluded that the dominant origin of multiple breast cancers is intramammary spread from a single primary tumor, although some cases arise by independent pathogenic processes. Recently, Brommesson et al [23] compared genomic similarities among synchronous multiple invasive breast cancers by microarray-based comparative genomic hybridization and found that 5 of 10 unilateral tumor pairs displayed similar genomic profiles, suggesting that some synchronous unilateral multiple tumors can have a common origin, whereas others arise independently.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, Teixera et al [21,22], using cytogenetic analysis, concluded that the dominant origin of multiple breast cancers is intramammary spread from a single primary tumor, although some cases arise by independent pathogenic processes. Recently, Brommesson et al [23] compared genomic similarities among synchronous multiple invasive breast cancers by microarray-based comparative genomic hybridization and found that 5 of 10 unilateral tumor pairs displayed similar genomic profiles, suggesting that some synchronous unilateral multiple tumors can have a common origin, whereas others arise independently.…”
Section: Discussionmentioning
confidence: 98%
“…Imyanitov et al determined status for all but one of 28 investigated cases, using 14 fixed markers for each tumor [5], showing a higher similarity between synchronous CBC than metachronous CBC. Two studies have used CGH to investigate the relationship between the tumors, showing that investigation of genomic imbalances can be used to detect recurrent breast tumors in both the ipsilateral and contralateral settings [6,7]. In each study, a single patient was detected to have a metastasis instead of a second primary, out of 8 bilateral cases in the Brommesson et al study, and 9 bilateral cases in the Teixeira et al study.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that for a subset of the patients, the second cancer is not a new primary tumor, but instead a metastasis of the first cancer, which could, in part, explain the poor prognosis of these patients. Several [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…show some CBC to have features similar enough to BC1 that a metastatic spread is possible (11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%